Computational Study of Amorphous Phase Formation in Ti53Cu39Ni8 and Ti50Cu42Ni8 Alloys - Nayara Pinel Silva; Verona Biancardi Aguiar; Luis César Rodríguez Aliaga (Materials Research, 2025)
Ti-based amorphous alloys are promising for biomedical applications due to their high mechanical strength, low modulus of elasticity, corrosion resistance, and biocompatibility. This study primarily utilized molecular dynamics simulations to investigate the glass-forming behavior of Ti53Cu39Ni8 and Ti50Cu42Ni8 alloys, using the LAMMPS code with a hybrid potential composed of the modified embedded atom method and Lennard-Jones potentials. Structural properties were analyzed using X-ray diffraction, pair distribution functions, and Voronoi polyhedra. The variation in viscosity with temperature in the supercooled liquid during cooling was calculated using the Green-Kubo method. Liquidus (TL) and solidus (TS) temperatures were determined from heating curves obtained at a rate of 1 K/ps. The glass transition temperatures (Tg) were obtained from cooling curves and compared with experimental measurements. Simulated and experimental XRD results confirmed that both alloys are fully amorphous, with TL, TS, and Tg increasing with higher titanium content. The reduced glass transition temperatures (Trg = Tg/Tₗ) were 0.437 for Ti53Cu39Ni8 and 0.430 for Ti50Cu42Ni8. The viscosity change was more pronounced in the Ti50Cu42Ni8 alloy, indicating greater thermal stability of the supercooled liquid near Tg, attributed to an increase in icosahedral clusters, reaching a 6% volume fraction at 300 K. Additionally, the predicted values of Tg from the simulations are in good agreement with experimental measurements.